Development of E-Module Integrated STEM Approach to Improve Students' Critical and Creative Thinking Skills - Tri Zeni Adha; Asrizal Asrizal; Fanny Rahmatina Rahim (Department of Physics Universitas Negeri Padang, 2023)
The era of industrial revolution 4.0 aims to develop human resources who can discuss creatively and think critically. Teachers can take advantage of technological developments by designing e-modules that integrate with STEM approaches that improve students' critical and creative thinking skills. The purpose of this study was to determine the results of validation of integrated e-modules the STEM approach. This research belongs to the research and development that designs up to the demonstration test stage using a four-dimensional development model. The data collection tool used validation sheets. The data collection tool used validation sheets. The result obtained from the mean V is 0.68, which is within the valid category. Based on the results of the study, it was concluded that an integrated work and energy materials e-module using a STEM approach would be suitable for use in a Grade X physics class. The e-modules integrated with STEM approach will be further developed and used as standalone learning materials to overcome the challenges of Industrial Revolution 4.0. This enhances student ability to think critically and creatively, leading to meaningful learning